TEACHING THE DIVINE IN EARLY ISLAMIC EDUCATION: NARRATIVE APPROACHES AND PEDAGOGICAL STRATEGIES AMONG MUSLIM PRESCHOOL TEACHERS - Al-Razi, Muhammad Fakhruddin; Madjid, Abd. (Balai Penelitian dan Pengembangan Agama Jakarta, 2025)
Teaching the concept of divinity in Islam, which tends to be abstract, to preschool children is a challenge, given their immature cognitive modalities. To this end, this article explores teachers' approaches and narrative models used in providing divinity education to Muslim children. Semi-structured interviews with Muslim teachers who have more than one year of experience teaching preschool children show that the approaches and narrative models used by the teachers vary widely and tend to be eclectic. Teachers tend to introduce and relate children to the concept of divinity through habituation and religious terms rather than teaching the concept of divinity in detail to children. The approaches used by teachers are linguistic and habituation approaches. The narratives used are body analogies, natural phenomena, simple associations, and chants or nadzam (Arabic poetry) that are recited and memorized together. These findings make an important contribution to the development of contextualized and developmentally appropriate divinity education methods in an Islamic cultural environment.